2020
DOI: 10.1111/ijcp.13620
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and readiness to test for COVID‐19; A qualitative exploration of community pharmacists

Abstract: Since December 2019, a viral outbreak has emerged in Wuhan city, Hubei province in China, which was caused by very contagious and rapidly spreading novel virus. 1 This virus was isolated and discovered by Chinese scientists on the 7th January 2020 2 and was termed coronavirus disease 2019 (COVID-19) by the World Health Organization (WHO) in February 2020. 3,4 COVID-19 has been reported as an extraordinary virus in its spreading rate where it has disseminated outstandingly, affecting many countries around the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Nowadays, the world is facing a predatory pandemic infection caused by the COVID‐19 requiring a concerted effort by healthcare professionals and public health experts to contain the rate of infection and the havoc it wreaks. Pharmacists, as essential health service providers, are important in the management and control of COVID‐19 16,26,27 . Hearteningly, the results of this survey indicated that pharmacists in the Arab‐speaking countries in the MENA region have a good awareness about the COVID‐19 and acknowledge the different roles they can play during these times.…”
Section: Discussionmentioning
confidence: 87%
“…Nowadays, the world is facing a predatory pandemic infection caused by the COVID‐19 requiring a concerted effort by healthcare professionals and public health experts to contain the rate of infection and the havoc it wreaks. Pharmacists, as essential health service providers, are important in the management and control of COVID‐19 16,26,27 . Hearteningly, the results of this survey indicated that pharmacists in the Arab‐speaking countries in the MENA region have a good awareness about the COVID‐19 and acknowledge the different roles they can play during these times.…”
Section: Discussionmentioning
confidence: 87%
“…The test format needs to be compatible with large scale production, which in the case of COVID19 was possible for tests that were supported on pre existing platforms 43 . Any test that was developed rapidly but was not applicable on an existing instrument had a sub stantial disadvantage to reach the market 44 . Possible exceptions are tests that are presented in a platform agnostic layout and that can be combined with any type of instrument already available to laboratory based diagnosticians 45 .…”
Section: Considerations For the Development Production And Distributmentioning
confidence: 99%
“…The confinement context defined how to involve the participants in the study, facilitating the best suitable way for them to respond to the questions and offering the possibility to do it by email, telephone, and WhatsApp. Non-face-to-face technologies have been used in the COVID-19 context to develop qualitative research in different fields of knowledge, such as clinical psychology or medicine [52,53]. The dialogue between researchers and social workers underlined this process to agree about when to develop the semi-structured interview.…”
Section: Data Collection and Analysismentioning
confidence: 99%